Kebuntingan Hasil Transfer Blastosis Mencit yang Dibekukan dengan Metode Vitrifikasi Kriolup - Batan, I Wayan; Suatha, I Ketut; Djuwita, Ita; Handhayani, Nining; Esti Prasetyaningtyas, Wahono; Adnyane Mudite, Ketut; W Lay, Bibiana; -, Supar; Boediono, Arief (Jurnal Veteriner, 2012)
The aim of the study was to assess the viability of vitrified embryo using cryoloop as a carrier ofembryo. The blastocyst stage embryos were collected from superovulated mice. Embryos were frozenusing vitrification method and vitrified embryos were loaded on copper filament cryoloop before dipped inliquid nitrogen. The viability of vitrified embryos was assess in vitro by medium cultered and in vivo bytransfered them to recipient mice. The result shows the viability of vitrified embryos was 85,7% after 24hours cultured and the embryos were born from two pregnant recipient mice out of nine (22%) or fouroffspring out of 63 trasfered embryos (6%). In conclusion, vitrified blatocyst stage embryos using cryoloopas a carrier could keep the viability of the embryos and they could be transfered to the recipient mice andwere born normally.
Keywords: embryo trasfer, blastocyst, vitrification, cryoloop